Sustainable water management in slaughterhouses by cleaner production methods-a review - Bailone, Ricardo [UNESP]; Roca, Roberto [UNESP]; Fukushima, Hirla; Aguiar, Luis Kluwe de (Cambridge Univ Press, 2021)
The demand for water is high in the food industry, particularly during the processing of animal product origin. A more sustainable approach to the use of the water resource is needed to reduce its waste. A systematic literature review was carried out from publications identified according to relevance and timeliness. The aim was to find alternative food processing production methods that considered both recycling and reuse of water in different slaughtering of animals such as cattle, swine, poultry, goat, sheep and fish. Articles which addressed cleaner production methods were selected because of special relevance in water resource management, Poultry processing was considered a special case regarding the recycling and reuse of water. That was due to the volume of water used as well as the level of likely contamination it might pose if reused. Wastewater can be largely reduced by adopting changes in practices, such as plant layout; materials used; drainage systems using dedicated separation of effluents and shaded area at reception with ventilation and sprinkles.
Keywords: Animal processing; sustainability; waste water reduction; water management